Legal Review of Government Regulation No. 56 of 2021 on Copyright Royalties Management for Songs and or Music in Broadcasting Media with Focus on Radio - Rustianto, Maulana Yusuf; Yestati, Ariani; Januardy, Ivans (Dinasti Research, 2025)
Broadcast media plays an important role in disseminating information, entertainment, and culture to the public. In Indonesia, radio, as one of the oldest and still relevant media, has an important function in promoting musical works, including disseminating copyrighted songs. However, the use of songs on the radio must comply with applicable legal provisions, including the obligation to pay royalties to copyright owners through collective management institutions, such as LMKN based on Government Regulation Number 56 of 2021. This study aims to review the legal regulations related to the use of songs by radio stations within the framework of copyright royalty management, as well as transparent and effective royalty management mechanisms. The method used is normative legal research with an analysis of primary and secondary legal sources related to PP No. 56 of 2021 and Copyright regulations. The results of the study show that the implementation of these regulations has challenges, such as minimal socialization, complex procedures, and limited supervision. However, the implementation of the royalty management mechanism through LMKN can help protect the rights of creators while supporting the interests of the broadcasting industry. The need for increased socialization, a simpler reporting system, and effective supervision are strategic recommendations to ensure the success of song copyright royalty management on the radio.